2020
DOI: 10.1136/tsaco-2020-000483
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter assessment of the Brain Injury Guidelines and a proposal of guideline modifications

Abstract: BackgroundThe Brain Injury Guidelines provide an algorithm fortreating patients with traumatic brain injury (TBI) and intracranial hemorrhage(ICH) that does not mandate hospital admission, repeat head CT, orneurosurgical consult for all patients. The purposes of this study are toreview the guidelines’ safety, to assess resource utilization, and to proposeguideline modifications that improve patient safety and widespreadreproducibility.MethodsA multi-institutional review of TBI patients was conducted. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 27 publications
3
36
0
Order By: Relevance
“…7,8,13,14 Over time, these guidelines have evolved, with some modifications, to a mainstay in the management of acute TBI patients, particularly in non-trauma centers. 15 Analysis of BIG by outside institutions has found statistically significant increased rate of progression in BIG 1 and 2 groups who have EDH or IPH. Other risk factors for radiologic progression of ICH were found to be alcohol consumption, age greater than 65, skull fractures, and usage of anticoagulants (for age over 65).…”
Section: Discussionmentioning
confidence: 99%
“…7,8,13,14 Over time, these guidelines have evolved, with some modifications, to a mainstay in the management of acute TBI patients, particularly in non-trauma centers. 15 Analysis of BIG by outside institutions has found statistically significant increased rate of progression in BIG 1 and 2 groups who have EDH or IPH. Other risk factors for radiologic progression of ICH were found to be alcohol consumption, age greater than 65, skull fractures, and usage of anticoagulants (for age over 65).…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter retrospective assessment found that improvements were needed to ensure patient safety and to clarify several aspects of the BIG to allow them to be consistently reproduced. 4 The mBIGs were created to accomplish both of these tasks. In order to improve patient safety, all EDHs are characterized as mBIG 3 under the modified guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The BIG are not perfect, however. A multicenter retrospective assessment found that improvements were needed to ensure patient safety and to clarify several aspects of the BIG to allow them to be consistently reproduced 4 . The mBIGs were created to accomplish both of these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of changes made over iterations include refining comorbidity codes for preexisting anemia and coronary disease for red blood cell (RBC) transfusion and refining Abbreviated Injury Scale codes for Brain Injury Guidelines criteria for mild complicated traumatic brain injury (TBI). 33…”
Section: Qi Metricsmentioning
confidence: 99%